“Naturam ars imitatur”: Magical images within Marsilio Ficino’s De Vita Libri Tres - Beiweis, Susanne K. (Verbum – Analecta Neolatina, 2018)
This article analyses the philosophical discussion of magic in De vita libri tres (1489), written by the fifteenth-century philosopher Marsilio Ficino (1433–1499). Through a close reading of passages on magical talismans and objects (such as a cubiculum,) the paper argues that Ficino not only expounded his ambivalent metaphysical theories on matter and form but also eroded the formula of naturam ars imitatur. Ficino’s discussion of magic thus oscillates between a re-interpretation of classical and medieval magic theories and a new cultural and scientific self-understanding of the individual as artifex of nature.